The Influence of Service Quality and Product Quality on Customer Trust and Loyalty at Perumda Air Minum Jaya (PAM JAYA) - Muhammad DAFIQ; Aldina SHIRATINA (PT Keberlanjutan Strategis Indonesia, 2024)
This research aims to determine the service quality and product quality of customer trust and loyalty of PERUMDA AIR MINUM JAYA (PAM JAYA), both directly and through intervening variables or indirect effects. This study uses a quantitative approach to explain the positions of the variables studied and the relationships between one variable and another. This research will demonstrate the causal relationships between variables through hypothesis testing. The data analysis technique is SEM-PLS with a total sample size. The study results show that all seven hypotheses proposed in the SEM-PLS model are accepted. This research implies that the management of PERUMDA AIR MINUM JAYA (PAM JAYA) is advised to conduct regular training for employees to improve their ability to provide responsive and professional services.